2021
DOI: 10.3390/admsci11020046
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Elements for Quality Assurance of Health Worker Protection Measures in Times of COVID-19 Pandemic

Abstract: The COVID-19 (coronavirus disease) pandemic has had a significant impact on the healthcare delivery system worldwide. Many pre-pandemic norms, standards, and methods of providing medical services in most medical facilities had to be changed and re-evaluated. Many of them will likely stay changed and will probably never be provided in the same way in post-pandemic reality. The COVID-19 crisis is still ongoing and some sources say that we should be prepared for a third wave of the pandemic. The scope of the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…As the number of internet users increases, more and more people will be able to access e-learning platforms to take courses or complete degrees. In addition to education, the use of remote work methods [26][27][28] and tools [29][30][31][32] is also observed in different work areas. The COVID-19 pandemic had a strong impact on e-learning popularization and the change in the usage of innovative e-learning tools in university education [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the number of internet users increases, more and more people will be able to access e-learning platforms to take courses or complete degrees. In addition to education, the use of remote work methods [26][27][28] and tools [29][30][31][32] is also observed in different work areas. The COVID-19 pandemic had a strong impact on e-learning popularization and the change in the usage of innovative e-learning tools in university education [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, studies that look for strengths and weaknesses, such as those related to the construction of public healthcare systems that made it possible to counteract the consequences of the pandemic effectively, have become popular. For example, studied the behavioral intentions of the population to get vaccinated and predicted the consequences of the speed of the spread of the virus [ 5 ]; looked in detail at tools that help increase the effectiveness of public health in EU countries [ 6 ]; in researchers developed road maps for possible future epidemiological threats to ensure public health at a sufficient level [ 7 ]; while investigating the problem of child mortality, identified a particular set of stabilizers in the organization of health care [ 8 ]; considered the role of mass media in covering the actual situation with the pandemic [ 9 ]; saw a relationship between the duration and severity of quarantine on the one hand, and the speed of disease spread on the other [ 10 ]; examined the degree of protection of doctors against diseases while working with patients [ 11 ]; came to the conclusion that due to the additive economy, namely the increase in production efficiency, it is possible to achieve a reduction in social risks, including in the medical field [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Popular new research domains include, for example, artificial intelligence [ 15 ], virtual reality [ 14 , 16 ], augmented reality [ 17 , 18 ], and many more. Naturally, the use of remote work methods [ 19 , 20 , 21 ] and digital tools [ 22 , 23 , 24 , 25 ] is observed not only in education, but also in different work areas.…”
Section: Introductionmentioning
confidence: 99%
“…Based on analysis of the literature [ 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], the authors have found the research gap in the case of the influence of the COVID-19 pandemic on the use of innovative e-learning tools in high education. The main problem that was analyzed in the paper was the influence of the COVID-19 pandemic on the change in the usage of innovative e-learning tools in university education.…”
Section: Introductionmentioning
confidence: 99%